Towards a common vision for climate change, security and migration in the Mediterranean - Mastrorillo, Marina; Scartozzi, Cesare Marco; Pacillo, Grazia; Menza, Gianpiero; Desai, Bina; Maviza, Gracsious; Jaskolski, Martina; Schapendonk, Frans; Meddings, George; Carneiro, Bia; Craparo, Alessandro; Minoarivelo, Henintsoa Onivola; et al. (2024)
Increasing evidence indicates that climate change is likely to amplify risks and insecurities, leading to increased fragility and conflict (IPCC, 2022). Climate change can exacerbate food insecurity and fosters climate-induced mobility, thereby straining socio-economic systems and increasing the potential for disputes over dwindling natural resources. At the same time, conflict and fragility have proven to impede efforts to enhance climate resilience and adaptive capacity, leaving populations more vulnerable to climate impacts and exacerbating food insecurity (Scartozzi, 2020). The Mediterranean is one of the most vulnerable areas to climate risks. The region is exposed to recurrent droughts, heat waves and other slow-onset climate events, which are leading to soil degradation and water shortages. Moreover, the region already accommodates half of the global populace grappling with water scarcity—a situation projected to further deteriorate due to climate change (ARLEM, 2021). Scientists warn that absent robust measures to manage and mitigate climate change, its adverse impact could overwhelm the adaptive capacity of the Mediterranean countries, weakening institutions and potentially exacerbating conflicts over natural resources (Scheffran, 2020). Currently the agricultural output in the Mediterranean is declining due to climate change, unsustainable agricultural practices, and water scarcity. These issues, combined with the region's growing population, pose significant challenges to sustaining living standards and development opportunities. Furthermore, food security is threatened by unsustainable human activities, such as deforestation, excessive water use in irrigation, and overuse of chemical fertilizers and pesticides. These actions, compounded by climate change impacts, exacerbate the region's growing demand for food, which in turn heightens its reliance on imports, making it increasingly susceptible to international price fluctuations. Climate change, socio-economic insecurity and political instability are pushing countries to critical levels of fragility. In the most affected regions, these factors are fostering grievances that can result in forms of organized violence and conflict. While the food-land-water nexus represents a potential intersection where to mitigate these tensions, conflict, poverty, and a lack of opportunities for youth—exacerbated by environmental and climate change—compel migration within and across regions, which often occurs through unsafe channels, including the perilous journey across the Mediterranean Sea. Additionally, the challenge is intensified by the lack of cohesive long-term governance and a common vision among agricultural resource management authorities and policy actors, leading to disparate efforts in addressing these issues (ARLEM, 2021). Improving people’s resilience in the region strongly depends on the ability to enhance the regional adaptive capacity to climate risks. The way governments and communities manage resources and food systems is a determinant factor in whether the Mediterranean area can endure development and peace. With no peace, there is no space for development. With no development, economic opportunities and food security, peace cannot last. This white paper is the result of a high-level discussion carried out at the event “Towards a Common Vision of the Climate, Migration and Security Nexus in the Mediterranean Region,” organized by the CGIAR Focus Climate Security and the Alliance of Bioversity & CIAT, and held in Rome in June 2023. The discussion collected opinions of scientists, politicians, experts and representatives of relevant international organizations on the climate-security-mobility nexus in the Mediterranean. The purpose of the discussion was to analyze current and foreseen vulnerabilities, risks and hazards affecting livelihoods in the region, and identify potential solutions and integrated approaches to increasing climate adaptation capacities, reducing involuntary and unsafe migration, and sustaining peace and stability.